Silencing of the 20S proteasomal subunit-α6 triggers full oogenesis arrest and increased mRNA levels of the selective autophagy adaptor protein p62/SQSTM1 in the ovary of the vector Rhodnius prolixus. - Allana Faria-Reis; Samara Santos-Araújo; Jéssica Pereira; Thamara Rios; David Majerowicz; Katia C Gondim; Isabela Ramos (Public Library of Science (PLoS), 2023)
The high reproductive rates of insects contribute significantly to their ability to act as vectors of a variety of vector-borne diseases. Therefore, it is strategically critical to find molecular targets with biotechnological potential through the functional study of genes essential for insect reproduction. The ubiquitin-proteasome system is a vital degradative pathway that contributes to the maintenance of regular eukaryotic cell proteostasis. This mechanism involves the action of enzymes to covalently link ubiquitin to proteins that are meant to be delivered to the 26S proteasome and broken down. The 26S proteasome is a large protease complex (including the 20S and 19S subcomplexes) that binds, deubiquitylates, unfolds, and degrades its substrates. Here, we used bioinformatics to identify the genes that encode the seven α and β subunits of the 20S proteasome in the genome of R. prolixus and learned that those transcripts are accumulated into mature oocytes. To access proteasome function during oogenesis, we conducted RNAi functional tests employing one of the 20S proteasome subunits (Prosα6) as a tool to suppress 20S proteasomal activity. We found that Prosα6 silencing resulted in no changes in TAG buildup in the fat body and unaffected availability of yolk proteins in the hemolymph of vitellogenic females. Despite this, the silencing of Prosα6 culminated in the impairment of oocyte maturation at the early stages of oogenesis. Overall, we discovered that proteasome activity is especially important for the signals that initiate oogenesis in R. prolixus and discuss in what manner further investigations on the regulation of proteasome assembly and activity might contribute to the unraveling of oogenesis molecular mechanisms and oocyte maturation in this vector.